Vitamin E D-alpha-tocopheryl polyethylene glycol 1000 succinate-conjugated liposomal docetaxel reverses multidrug resistance in breast cancer cells. (18th June 2019) - Li, Na; Fu, Tingting; Fei, Wenling; Han, Tianyan; Gu, Xiangshuai; Hou, Yanhui; Liu, Yanhua; Yang, Jianhong
Abstract: Objectives: Multidrug resistance (MDR) remains a primary challenge in breast cancer treatment. In the present study, D-alpha-tocopheryl polyethylene glycol 1000 succinate (TPGS)-coated docetaxel-loaded liposomes were developed as a novel drug delivery system to reverse MDR and enhance breast cancer therapy compared with the traditional liposomes, DSPE-mPEG-coated liposomes (stealth liposomes) and commercial Taxotere®. Key findings: Liposomes were prepared by thin – film dispersion method. Evaluations were performed using human breast cancer MCF-7 and resistant MCF-7/ADR cells. The reversal multidrug-resistant effect was assessed by P-gp inhibition assay, cytotoxicity, cellular uptake and apoptosis assay. Results: The TPGS-chol-liposomes were of an appropriate particle size (140.0 ± 6.0 nm), zeta potential (−0.196 ± 0.08 mv), high encapsulation efficiency (99.0 ± 0.9) and favourable in vitro sustained release. The TPGS-coated liposomes significantly improved cytotoxicity and increased the intracellular accumulation of docetaxel in both types of breast cancer cells. The TPGS-coated liposomes were confirmed to induce apoptosis via a synergistic effect between docetaxel and TPGS. It was demonstrated that TPGS enhanced the intracellular accumulation of drug by inhibiting overexpressed P-glycoprotein. Conclusions: The TPGS-conjugated liposomes showed significant advantages in vitro compared with the PEG-conjugated liposomes. The TPGS-conjugated liposomes could reverse the MDR and enhance breast cancer therapy.